Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
A (-4,5) B (-3,1) C (-5,2) D (3,1) E (2,5) F(4,4)
Step-by-step explanation:
Transformation involves changing the position of a shape.
The transformation rule is: [tex]\mathbf{(x,y) \to (-x - 1,-y + 6)}[/tex]
From the graph, we have the following points
[tex]\mathbf{A = (-4,5)}[/tex]
[tex]\mathbf{B = (-3,1)}[/tex]
[tex]\mathbf{C = (-5,2)}[/tex]
First, triangle ABC is reflected across the x and y axes.
So, we have:
[tex]\mathbf{(x,y) \to (-x,-y)}[/tex]
Next, the points are shifted up by 6 units, and left by 1 unit.
So, we have:
[tex]\mathbf{(x,y) \to (-x - 1,-y + 6)}[/tex]
Apply the above transformation rule on ABC, we have:
[tex]\mathbf{C = (4 - 1,-5 + 6) = (3,1)}[/tex]
[tex]\mathbf{D = (3 - 1,-1 + 6) = (2,5)}[/tex]
[tex]\mathbf{E = (5 - 1,-2 + 6) = (4,4)}[/tex]
Hence, the transformation rule is: [tex]\mathbf{(x,y) \to (-x - 1,-y + 6)}[/tex]
And the image of the transformation are:
[tex]\mathbf{D = (3,1)}[/tex] [tex]\mathbf{E = (2,5)}[/tex] [tex]\mathbf{F = (4,4)}[/tex]
Read more about transformation at:
https://brainly.com/question/11707700
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.